Design of tools to reduce the risk level of work postures at warping station - Wardani, Indira Kusuma; Iftadi, Irwan; Astuti, Rahmaniyah Dwi (Jurnal Sistem dan Manajemen Industri, 2020)
Based on the REBA analysis, there is a risky operator work postures in the warping work station at PT. Iskandar Indah Printing Textile because they do not use work tools. The assessment of the level of work posture risk by the REBA method gets the result that the highest work element with a final score of 10 is obtained by taking warp yarn at the warping station. This study aims to produce a design tool to reduce the level of work posture risk in warping work station operators. Then the design of tools was carried out by the Pahl and Beitz method to produce three alternative product design concepts. Based on the three ideas, the best plan is chosen by using an Engineering Design Selection, and the result is the second design concept. The selected design is an adjustable trolley with a vertical screw drive system that is comfortable to use and does not cause a bending position on the operator because it has a trolley plate that can be adjusted in height as needed. The use of the trolley causes a decrease in the level of work posture risk from a high-risk level to a small risk level with a final score of 10 to 3.